2019
DOI: 10.1145/3299903
|View full text |Cite
|
Sign up to set email alerts
|

Strong Steiner Tree Approximations in Practice

Abstract: In this experimental study we consider Steiner tree approximation algorithms that guarantee a constant approximation ratio smaller than 2. The considered greedy algorithms and approaches based on linear programming involve the incorporation of k-restricted full components for some k ≥ 3. For most of the algorithms, their strongest theoretical approximation bounds are only achieved for k → ∞. However, the running time is also exponentially dependent on k, so only small k are tractable in practice.We investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The closest works to ours consist of experimental studies [7,12,23,[32][33][34]39], software packages implementing various algorithms (GeoSteiner [41], SCIP-Jack [33]), and benchmark suites (SteinLib [26], PACE2018 [31], Vienna [29]) for the Steiner tree problem and its variants. To the best of our knowledge there are no previous experimental studies on approximation algorithms for Steiner forest.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The closest works to ours consist of experimental studies [7,12,23,[32][33][34]39], software packages implementing various algorithms (GeoSteiner [41], SCIP-Jack [33]), and benchmark suites (SteinLib [26], PACE2018 [31], Vienna [29]) for the Steiner tree problem and its variants. To the best of our knowledge there are no previous experimental studies on approximation algorithms for Steiner forest.…”
Section: Related Workmentioning
confidence: 99%
“…FIGURE7 Complete graphs with Euclidian weights (selected instances): Running time and cost of solution (The main horizontal axis shows the key parameters of each instance as a pair (n, k), while the secondary horizontal axis shows the corresponding test set. The instances are listed in nonincreasing order of the number of vertices from left to right.…”
mentioning
confidence: 99%
“…However, Warme [234] showed that if the size of the maximum FSC is bounded by a constant, then the LP‐relaxation of HYP can be obtained in polynomial time. This fact has been extensively exploited in a series of articles that provide LP‐based approximation algorithms for the STP [23, 25, 37, 110, 147] (cf. Section 9).…”
Section: Mip Formulations and Relaxationsmentioning
confidence: 99%
“…Approximation algorithms based on hypergraphic LP‐relaxations have been implemented and empirically tested by Beyer et al [23, 25]; see also Section 9. However, to the best of our knowledge, there are no empirical studies on exact methods for the STP in graphs derived from HYP.…”
Section: Mip Formulations and Relaxationsmentioning
confidence: 99%
See 1 more Smart Citation